the effect of think – aloud strategy on the results of the fifth – grade students in the geography subject Search of preparation (Journal of the College of Basic Education, 2019)
Aims research sought to acknowledge ( the effect of think – aloud strategy on the results of the fifth – grade students in the geography subject ) .In order to verify the objective of the research and its hypothesis , a sample of fifth grade students were selected in the city of Baghdad belonging to the general directorate of the Baghdad for the Secondary merning schools / Rasafa second district.Two groups of fifth – grade girls , both experimental and disciplined , were selected from the sumer girls secondary school , the study sample were 67 female students , 34 female students in the experimental group , and 33 students in the disciplined group ,Were the researcher did a equivalence in variables test ( age , academical achievement of the previous year in geography ) before doing the test and no statistical differences between the two groups were found .The results of the study showed that the students of the experimental group who studied natural geography using the " think – aloud " strategy was superior to the group of the elite and disciplined students when it came to the eligibility test .